Expanding the STEM integration model introducing the learning environment - Svendsen, Maiken Westen Holm; Larsen, Dorte Moeskær; Svabo, Connie (LUMAT: International Journal on Math, Science and Technology Education, 2025)
The increasing demand for a future-ready workforce, driven by rapid technological advancements, has positioned STEM (Science, Technology, Engineering, and Mathematics) education as a global priority. Despite its recognized importance, integrating STEM within traditionally monodisciplinary educational systems poses significant challenges. These include rigid curricula, subject compartmentalization, and institutional constraints that hinder interdisciplinary collaboration. This study aims to address these challenges by proposing an expansion of the existing STEM integration model developed by Seidelin and Larsen in 2021, which originally includes four approaches: content integration, overlapping methods integration, overlapping concepts integration, and context integration. The proposed expansion introduces a fifth element focused on the learning environment, recognizing the critical role that physical spaces, local contexts, and materials play in shaping integrated STEM education. The study draws on insights from the Danish LabSTEM+ project, where educators utilized what the project calls a laboratory model to explore the impact of the learning environment on STEM teaching. Methods included field observations, interviews, and the analysis of four case studies involving diverse educational contexts. The results demonstrate that the learning environment serves as a new way of integrating STEM. This addition of a fifth element to the integration model by Seidelin and Larsen offers a more comprehensive framework for STEM integration. The study concludes that the learning environment can be seen as a core component of developing integrated STEM teaching.